Psychological Distress and Poor Quality of Life in Patients with Central Serous Chorioretinopathy. (March 2014) - Şahin, Alparslan; Bez, Yasin; Kaya, Mehmet Cemal; Türkcü, Fatih Mehmet; Şahin, Muhammed; Yüksel, Harun
Abstract Purpose: We aimed to compare the mental health and quality of life (QoL) between central serous chorioretinopathy (CSCR) patients and the control subjects. Methods: Thirty consecutive patients presenting with CSCR and age-gender-matched 30 healthy control subjects filled in the following standardized questionnaires: Symptom Checklist 90-R (SCL 90-R) and Short Form 36 (SF-36). Age, gender, and ocular clinical findings were recorded. Results: According to SCL-90-R, all scores were significantly higher in the CSCR group when compared to the control group. The patients with CSCR reported significantly lower levels of QoL, except bodily pain. Conclusion: Our results indicated that CSCR patients have poorer QoL and more psychological problems. CSCR patients may benefit from psychosocial support and interventions.